Fabrication of Ciprofloxacin-Loaded Sodium Alginate Nanobeads Coated with Thiol-Anchored Chitosan Using B-390 Encapsulator Following Optimization by DoE - Mahwash Mukhtar; Ildikó Csóka; Josipa Martinović; Gordana Šelo; Ana Bucić-Kojić; László Orosz; Dóra Paróczai; Katalin Burian; Rita Ambrus (MDPI AG, 2024)
Most infectious diseases of the gastrointestinal tract can easily be treated by exploiting the already available antibiotics with the change in administration approach and delivery system. Ciprofloxacin (CIP) is used as a drug of choice for many bacterial infections; however, long-term therapy and off-site drug accumulation lead to an increased risk of tendinitis and peripheral neuropathy. To overcome this issue, nanotechnology is being exploited to encapsulate antibiotics within polymeric structures, which not only facilitates dose maintenance at the infection site but also limits off-site side effects. Here, sodium alginate (SA) and thiol-anchored chitosan (TC) were used to encapsulate CIP via a calcium chloride (CaCl2) cross-linker. For this purpose, the B-390 encapsulator was employed in the preparation of nanobeads using a simple technique. The hydrogel-like sample was then freeze-dried, using trehalose or mannitol as a lyoprotectant, to obtain a fine dry powder. Design of Experiment (DoE) was utilized to optimize the nanobead production, in which the influence of different independent variables was studied for their outcome on the polydispersity index (PDI), particle size, zeta potential, and percentage encapsulation efficiency (% EE). In vitro dissolution studies were performed in simulated saliva fluid, simulated gastric fluid, and simulated intestinal fluid. Antibacterial and anti-inflammatory studies were also performed along with cytotoxicity profiling. By and large, the study presented positive outcomes, proving the advantage of using nanotechnology in fabricating new delivery approaches using already available antibiotics.